Chronic obstructive pulmonary disease and genetic predisposition (Environment & Health, 2017)
In Ukraine the largest part of the occupational morbidity of bronchopulmonary system is registered in the coal industry where the conditions of work are characterized by the impact of the high coal-rock dust concentrations in the air of working zone. Side by side with the industrial harmfulness, a long tobacco smoking affect the chronic obstructive pulmonary disease (COPD) development, infectious agents encourage progression and exacerbation of the disease. However, the scientific investigations demonstrate the impact of the genetic predisposition on the COPD development.Objective: We determined the main pathological mechanisms of the COPD formation. On the basis of the obtained data we analyzed the genes’ polymorphisms encoding the key links of disease pathogenesis. We determined the potential genetic markers of the COPD development that might improve a quality of the forecast and primary disease prevention in future.Results: Performed analysis demonstrated that the disturbance of the integrity of extra-cellular matrix, imbalance of the proteolysis-antiproteolysis system, oxidative stress, and inflammation in proximal and distal departments of low respiratory pathways affect the formation of the COPD. The genes of elastin (ELN), alpha-1-antitrypsin (SERPINA1), tissue inhibitors of matrix metalloproteinase (TIMPs), matrix metalloproteinase (MMPs), neutrophil elastase (NE), microsomal epoxide hydrolase (EPHX1), tumor necrosis factor α (TNF-α) were identified as the main gene-candidates of the COPD development.
Keywords: COPD; genetic predisposition; polymorphism